THE "TRIGATRA BAHASA": HOW MUCH DO DIGITAL NATIVE STUDENTS UNDERSTAND ABOUT IT? - Sunendar, Dadang; Hardini, Tri Indri; Racmadhany, Ariessa (International Journal of Education, 2024)
Global connectedness and the introduction of technology have made it possible for speakers of the three languages to communicate with each other on a larger scale in Indonesian context, commonly known as Trigatra Bahasa. Understanding language politics in Indonesia through Trigatra Bahasa with the slogan "Prioritize Indonesian, preserve regional languages, and master foreign languages" is an effort by the government to embrace all languages in Indonesia, especially among digital natives. This research aims to find out the extent of digital native students' understanding of the Trigatra Bahasa and to find out how they hope to understand the Trigatra Bahasa better. The method used was descriptive qualitative, and data were collected through questionnaires to 325 digital native students in West Java using a Likert scale with five assessment points. Before distributing the questionnaire, socialization was conducted so that these digital native students were familiar with Trigatra Bahasa. The results of this study show that most digital native students have a good understanding of the Trigatra Bahasa. They also strongly understand that the Trigatra Bahasa creates harmony in the language treasures of Indonesia. However, there is still a lack of familiarisation among them, so almost all respondents agree that an informative and interactive application related to Trigatra Bahasa is needed.